2020
DOI: 10.1158/1078-0432.ccr-19-1459
|View full text |Cite
|
Sign up to set email alerts
|

HIF-2 Complex Dissociation, Target Inhibition, and Acquired Resistance with PT2385, a First-in-Class HIF-2 Inhibitor, in Patients with Clear Cell Renal Cell Carcinoma

Abstract: Purpose: The heterodimeric transcription factor HIF-2 is arguably the most important driver of clear cell renal cell carcinoma (ccRCC). Although considered undruggable, structural analyses at the University of Texas Southwestern Medical Center (UTSW, Dallas, TX) identified a vulnerability in the a subunit, which heterodimerizes with HIF1b, ultimately leading to the development of PT2385, a first-in-class inhibitor. PT2385 was safe and active in a first-in-human phase I clinical trial of patients with extensive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(114 citation statements)
references
References 54 publications
(61 reference statements)
2
98
0
Order By: Relevance
“…GAGE analyses also identified a significant downregulation of the gene set HIF-2α Transcription Network, including Epo , Egln1 , Egln3 , Igfbp1, and Pfkfb3 . To further investigate potential overlap with recently defined HIF-2α-dependent genes in human ccRCC, we used a set of 277 genes that were identified as being inhibited specifically in tumour cells in ccRCC tumorgrafts in mice treated with the HIF-2α inhibitor PT2399 25 , 35 . Analyses of the expression levels of the mouse orthologues of this set of HIF-2α target genes revealed that many of these genes are highly upregulated in Vhl ∆/∆ Trp53 ∆/∆ Rb1 ∆/∆ tumours compared to WT cortex, but that the loss of either HIF-1α or HIF-2α did not broadly affect the upregulation of these genes (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GAGE analyses also identified a significant downregulation of the gene set HIF-2α Transcription Network, including Epo , Egln1 , Egln3 , Igfbp1, and Pfkfb3 . To further investigate potential overlap with recently defined HIF-2α-dependent genes in human ccRCC, we used a set of 277 genes that were identified as being inhibited specifically in tumour cells in ccRCC tumorgrafts in mice treated with the HIF-2α inhibitor PT2399 25 , 35 . Analyses of the expression levels of the mouse orthologues of this set of HIF-2α target genes revealed that many of these genes are highly upregulated in Vhl ∆/∆ Trp53 ∆/∆ Rb1 ∆/∆ tumours compared to WT cortex, but that the loss of either HIF-1α or HIF-2α did not broadly affect the upregulation of these genes (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As in other targeted therapy, therapeutic resistance is of a concern. For example, a gatekeeper mutation G323E in HIF-2α was identified to be responsible for PT2385 resistance after prolonged treatment (Courtney et al, 2020). Thus, further insights into the understanding of the MYC-HIF interplay are warranted for developing novel targeted therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…PT2385 also inhibited HIF-2α-driven gene expression and induced ccRCC tumor regression (Wallace et al, 2016). Recent result from a phase I clinic trial showed response, partial response or stable disease in ∼66% of patients with favorable safety profile and well tolerance for PT2385 (Courtney et al, 2018(Courtney et al, , 2020. Phase II clinic trials for PT2385 are ongoing in ccRCC (NCT03108066) and recurrent glioblastoma (NCT03216499).…”
Section: Targeting Myc-hif Crosstalk For Cancer Therapymentioning
confidence: 99%
“…Understanding the transcriptional regulation by HIFs has provided therapeutic targets currently under clinical evaluation 194,195 . Notably, HIF-2α inhibitors are being tested in renal cell carcinoma and pharmacologic inhibition of PHDs is being explored for the treatment of anaemia 196,197 . However, as conveyed in this article, cellular responses to hypoxia go much beyond the transcriptional networks governed by HIFs.…”
Section: Conclusion and Perspectivementioning
confidence: 99%